A Dynamic Threshold-Based Customer Redirection Rule for Minimizing Customer Transfer Costs in Bike-Sharing Systems - LORENZO, SIMON ANTHONY; LORENZO, LOWELL; MARTINEZ, IRIS ANN (Philippine Engineering Journal, 2021)
This paper produces a new dynamic threshold-based customer redirection rule that minimizes customer extra effort in bike-sharing systems while maintaining a target service level. The proposed rule entails the redirection of both the customer’s trip origin and destination following thresholds that are dynamically based on the stations’ forecast supply and demand for bikes. A simulation model based on London’s Santander Cycles bike-sharing system was used to evaluate the effectiveness of the proposed rule. Results show that the new rule was able to reduce the system average extra effort for customers by as much as 43.35% while maintaining the service level, over 100 replications of the simulation. Keywords — bike-sharing systems, customer redirection, extra effort minimization